Determinants of dividend policy of public listed company in Malaysia / Bartholomew Yusri - Yusri, Bartholomew (2020)
The purpose of this study is to focus on what does the listed company in Malaysia use a structure to make their dividend policy. With dividend per share as the dependent variable. The independent variable consists of Liquidity (LIQ), Leverage (LEV), Return on equity (ROE), Net profit Margin (NPM) and Earning per share (EPS). This study will also determine if NPM can be used as a determinant which the research gap in this study. The data was collected from the year 2015 to 2019 which was used in a panel data. The result from this study shows that LIQ, LEV and ROE have an insignificant with DPS compared to previous studies. Meanwhile, NPM and EPS can be used as a determinant because both variable have a significant relationship with DPS in public listed company in Malaysia.